2017
DOI: 10.1002/oby.21809
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and binge eating as mediators between posttraumatic stress disorder symptom severity and body mass index

Abstract: Objective Sexual minority women are at elevated risk for obesity, as well as of exposure to traumatic events. Rates of obesity are elevated in individuals with PTSD, but we know little about why this relationship exists. Behavioral mechanisms, such as eating patterns and alcohol use, are possible explanations that would be clinically useful to identify. Methods We longitudinally investigated binge eating and alcohol use as mediators of the relationship between PTSD symptom severity and body mass index (BMI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The current study also found that BMI was higher among women in the chronic stress exposure area than among those in the new‐onset stress expose area ( P < 0.001). This finding supports previous observations that chronic stress and post‐traumatic stress disorders are associated with increased BMI and eating disorders . In addition, in the chronic stress exposure area, there was a maternal trend toward DM when the repeated stressors occurred during the third trimester ( P =0.055).…”
Section: Discussionsupporting
confidence: 89%
“…The current study also found that BMI was higher among women in the chronic stress exposure area than among those in the new‐onset stress expose area ( P < 0.001). This finding supports previous observations that chronic stress and post‐traumatic stress disorders are associated with increased BMI and eating disorders . In addition, in the chronic stress exposure area, there was a maternal trend toward DM when the repeated stressors occurred during the third trimester ( P =0.055).…”
Section: Discussionsupporting
confidence: 89%
“…Another study identified emotional eating and physical activity self-efficacy as mediators [ 21 ], and another found no mediation by external or restrained eating [ 18 ]. In post-traumatic stress disorder, binge-eating, but not alcohol use, was a mediator [ 20 ]. In university students, emotional eating and food addiction were significant mediators of stress [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several of these lifestyle factors might mediate the relation towards weight change, e.g., diet-related factors such as emotional eating [ 17 , 18 ] and sleep [ 19 ] have been mentioned as mediators. Although multiple lifestyle factors play a role herein, only few studies [ 19 , 20 , 21 ] tested multiple mediation (i.e., independent mediation by several lifestyle factors at the same time) to identify the most important factor and whether a significant direct effect remained.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an overall measure of diet quality was used to measure eating behavior, but binge eating was not assessed. Two recent studies found that binge eating (Cronce et al, 2017) and disordered eating (Mitchell et al, 2016) explain the relationship between PTSD and Body Mass Index. Future studies should examine associations with different types of physical activity, given that a recent study found that hypervigilance interferes with vigorous physical activity, but not other physical activity levels (Harte et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with findings from a prospective study among 800 US Army soldiers, in which neither alcohol use nor smoking mediated the relationship between PTSD and somatic functioning (Vasterling et al, 2008). In addition, a recent study found that alcohol use did not mediate the relationship between PTSD and BMI (Cronce et al, 2017). Importantly, in the present study depression was associated with current smoking, which was associated with increased likelihood of diabetes, underscoring the need to address tobacco use among veterans with depression.…”
Section: Discussionmentioning
confidence: 99%